Sociodemographic Findings in an Infertile Male Population - Güngör, Tayfun; Kanat Pektaş, Mine; Günel, Müfit; Mollamahmutoğlu, Leyla (Gynecology Obstetrics & Reproductive Medicine, 2008)
OBJECTIVE: This research aims to identify the sociodemographic features of serious spermatogenetic disorders in infertile males. STUDY DESIGN: A total of 585 infertile men were eligible. Infertile men with abnormal physical findings were compared to infertile men with normal physical findings. Infertile men with severe spermatogenetic abnormalities (azoospermia and oligoasthenoteratozoospermia) were compared to infertile men with other spermatogenetic disorders. RESULTS: The majority of the subjects revealed no surgery, chronic disease, trauma, drug use or gonadotoxic exposure that could be related to their infertility. Testicular atrophy which was the most common physical finding, was significantly related to trauma. Subjects with abnormal physical findings were more likely to have severe spermatogenetic abnormalities which were directly correlated to gonadotoxic agents, particularly heat exposure. CONCLUSION: This study claims that the previously established risk factors which are considered to be associated with infertility might influence less or interfere with male infertility in more subtle ways.